"Dobro" razdolževanje podjetij v Sloveniji po začetku sanacije bank - Simoneti, Marko (Podjetje in delo, 2014)
In the broader context of bank rehabilitation and growing public debt in Slovenia the article presents proposals for starting the "good" deleveraging of companies that would limit negative impacts on economic growth. The differences between asset based and cash flow based lending are presented. It is demonstrated that the important problematic borrowers from banks balance sheets are not necessarily important for economic recovery and that companies with excessive debt owe a large portion of their liabilities to non-bank creditors. Therefore, for deleveraging of a big number of potentially viable companies it will be necessary to use various approaches, with most of the cases agreed between owners and active creditors out of court. The article analyses the opportunities for a broader use of debt-to-equity conversions and for separation of the healthy operational part of the firm, where the creditors are paid from cash flow, from the speculative investing part of the firm, where the creditors are paid from assets sale.
Keywords: banke; dolgovi; ekonomska kriza; insolventnost; krediti; podjetja; upniki